EVALUATION OF THE ROLE OF FINE-NEEDLE ASPIRATION CYTOLOGY IN DIAGNOSIS OF BREAST LESIONS AND CORRELATION WITH HISTOPATHOLOGICAL EXAMINATION - PALAK PATEL; Harsh Pandya; Avani Dangar; Drashti Patel; Krishna Kant Shiromani (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of this study is to assess the accuracy of fine needle aspiration cytology (FNAC) in the diagnosis of breast lesions in correlation with histopathological findings. Methods: This is a retrospective study for a period of 1 year of all the cases of breast lesions that were referred to the pathology department for FNAC and these patients were subjected to excisional biopsy/incisional biopsy/mastectomy. Results: In duration of 1 year of study, we received a total of 76 cases with complaints of breast lump. The frequency of benign breast lesions was higher in the range of 20–40 years and the frequency of malignant lesions was higher among the age group of 41–60 years. Out of 76 cases, 40 (52.6%) cases were of fibroadenoma, two (2.6%) cases were of abscess, two (2.6%) cases were of fibrocystic disease, two (2.6%) cases were of lactating adenoma and 30 (39.5%) cases were of a malignant lesion. Among the total of 76 cases, 46 cases were non-malignant and 30 cases were malignant on cytological examination. Forty-six non-malignant cases diagnosed on FNAC were correlated with histopathology examination. Two false negative cases were reported which were diagnosed as benign breast lesions turned out to be malignant on histopathological examination. Out of 30 diagnosed malignant lesions on FNAC, all were consistent with histopathology examination. In our study, the incidence of benign breast lesions is 57.9%, and malignant breast lesions are 39.5%, respectively. Conclusion: Our study states that reporting and findings of FNAC were closely correlated with the histopathological diagnosis in accordance with National Cancer Institute guidelines. FNAC has significant diagnostic value in differentiating breast lumps for further operative management. Awareness of breast cancer is a must and much needed in developing country like India which can be achieved by proper education, prevention, early detection, and proper management of breast lesions.